2020
DOI: 10.1088/1361-6579/abb4b3
|View full text |Cite
|
Sign up to set email alerts
|

Phantom material testing indicates that the mechanical properties, geometrical dimensions, and tensional state of tendons affect oscillation-based measurements

Abstract: Objective: There is an increasing interest in the application of oscillation-based measurement techniques to evaluate the mechanical stiffness of healthy and diseased tendons. These techniques measure the stiffness of a tendon indirectly by registering the oscillation response of a tendon to an external mechanical impulse. Although these measurement techniques seem to be comparatively easy and time-saving, their applicability is implicitly limited by their indirect measurement principle. Approach: In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…With this in mind, our study showed good estimated ICCs for the intra- and interrater reliabilities, but these results should be interpreted with caution due to the measurement error-related dropouts for a few data pairs, resulting in a smaller than the calculated sample size, and the 95% CIs indicated a large range from poor to excellent reliability. It should also be noted that myotonometry-based measurements record the transversal stiffness at the local measurement site of the tendon and could be affected by numerous tendon-related parameters ( 33 ). Therefore, it should be emphasized that stiffness measurements using myotonometry at loading conditions cannot be considered interchangeable with traditional procedures using synchronized force and ultrasound diagnostics ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…With this in mind, our study showed good estimated ICCs for the intra- and interrater reliabilities, but these results should be interpreted with caution due to the measurement error-related dropouts for a few data pairs, resulting in a smaller than the calculated sample size, and the 95% CIs indicated a large range from poor to excellent reliability. It should also be noted that myotonometry-based measurements record the transversal stiffness at the local measurement site of the tendon and could be affected by numerous tendon-related parameters ( 33 ). Therefore, it should be emphasized that stiffness measurements using myotonometry at loading conditions cannot be considered interchangeable with traditional procedures using synchronized force and ultrasound diagnostics ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Especially in sports with high vertical forces like jumping and sprinting, or those with high static contraction like hammer throw, muscles and tendons are exposed to a multiple of the individual’s bodyweight [ 34 ]. Due to repetitive training, tissue adaptions such as an increased tendon cross-sectional area and higher values of Young’s modulus can be observed [ 35 , 36 ]. Regular examinations with ultrasound and shear wave elastography are often still reserved for male athletes with better medical infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the amplitude and frequency of the sinusoidal curve are used as a surrogate measure of tendon stiffness ( Schneider et al, 2015 ). The easily accessible and cost-effective device has already been used in previous studies to test its validity and reliability and to detect changes in Achilles tendon stiffness non-invasively (for review see Sichting and Kram, 2020 ). Regarding the quality of stiffness assessment, several studies have demonstrated that the use of the handheld device produces valid ( Pruyn et al, 2016 ; Feng et al, 2018 ) and reliable results.…”
Section: Methodsmentioning
confidence: 99%